Regression models to assess the thermal performance of Brazilian low-cost houses: consideration of natural ventilation - Rossi, Michele Marta (2016)
Building performance simulations [BPS] tools are important in all the design stages, mainly in the early ones. However, some barriers such as time, resources and expertise do not contribute to their implementation in architecture offices. This research aimed to develop regression models (meta-models) to assess the thermal discomfort in a Brazilian low-cost house [LCH] during early design. They predicted the degree-hours of discomfort by heat and/or by cold as function of the design parameters changes for three Brazilian cities: Curitiba/PR, São Paulo/SP, and Manaus/AM. This work focused on using the meta-models to evaluate the impact of the parameters related to natural ventilation strategies on thermal performance in LCH. The analyzed Brazilian LCH consisted in a naturally ventilated representative unit developed based on the collected data. The most influential parameters in thermal performance, namely as key design parameters, were building orientation, shading devices positions and sizes, thermal material properties of the walls and roof constructive systems as well as window-to-wall ratios (WWR) and effective window ventilation areas (EWVA). The methodology was divided into: (a) collecting projects of Brazilian LCH, and based on that a base model that was able to represent them was proposed, (b) defining the key design parameters and their ranges, in order to compose the design space to be considered, (c) simulating thermal performance using EnergyPlus coupled with a Monte Carlo framework to randomly sample the design space considered, (d) using the greater part of the simulation results to develop the meta-models, (e)using the remaining portion to validate them, and (f) applying the meta-models in a simple design configuration in order to test their potential as a support design tool. Overall, the meta-models showed R2 values higher than 0.95 for all climates. Except for the regression models to predict discomfort by heat for Curitiba (R2 =0.61) and São Paulo (R2 =0.74). In their application, the models showed consistent predictions for WWR variations, but unexpected patterns for EWVA.